Simple Design of Polarization-Selective Tunable Triple Terahertz Absorber Based on Graphene Rectangular Ring Resonator - Jiang Wang; Haixia Zhu; Bo Ni; Minhao Zhou; Chengtao Feng; Haibin Ni; Jianhua Chang (Photonics)
In this paper, a simple design of a polarization-selective tunable triple terahertz absorber based on a graphene rectangular ring resonator was proposed and studied. The absorber structure consists of a graphene rectangular ring resonant array on the top, SiO2 dielectric layer in the middle and gold at the bottom. The calculated results show that the absorber can achieve high-efficiency triple-band absorption under both x and y polarization incident light. When x-polarized light is incident, three distinctive absorption peaks at 2.73, 5.70 and 11.19 THz with absorption rates of 96.7%, 98.5% and 96.5% are achieved. When y-polarized light is incident, three additional absorption peaks at 2.29, 7.55 and 9.98 THz can be obtained with absorption rates of 96.3%, 90.3% and 97.4%, respectively. Moreover, the absorption wavelength of the absorber can be tuned by adjusting the chemical potential of the graphene. Owing to the high efficiency of triple-band absorption in different polarization states, the absorber has broad application prospects in terahertz polarization imaging, sensing and detection.